Environmentally sustainable tourism as a strategic determinant of economic and social development - Vuković, Dijana; Hunjet, Anica; Kozina, Goran (Turizam, 2019)
While tourism industry can have a positive impact on social and economic development, its uncontrolled growth may cause substantial environmental damage and loss of local identity and traditional cultural values. The protection of biological, spatial and cultural values is imperative for sustainable tourist destinations to attract consumers. In a tourism analysis, natural attractions and the environment of a tourist destination are vital components of development. When choosing a travel destination, the perception of consumers affects the comparative advantage of the destination on the global tourism market, its reputation, its potential to attract and retain tourists, the quality of life and the standard of living of local residents, as well as potential investments. The paper aims to examine the environmental component as a strategic determinant of the development of a tourist destination. The paper investigates the many factors affecting the decisions of the management of a destination and looks in more detail at the pressures put by tourism activities on the eco-systems of travel destinations, which accelerate and intensify the consumption of destination values.